Simulations of atmospheric OH, O3 and NO3 reactivities within and above the boreal forest - D. Mogensen; R. Gierens; J. N. Crowley; P. Keronen; S. Smolander; A. Sogachev; A. C. Nölscher; L. Zhou; M. Kulmala; M. J. Tang; J. Williams; M. Boy (Atmospheric Chemistry and Physics, 2015)
Using the 1-D atmospheric chemistry transport model SOSAA, we have investigated the atmospheric reactivity of a boreal forest ecosystem during the HUMPPA-COPEC-10 campaign (summer 2010, at SMEAR~II in southern Finland). For the very first time, we present vertically resolved model simulations of the NO3 and O3 reactivity (R) together with the modelled and measured reactivity of OH. We find that OH is the most reactive oxidant (R ∼ 3 s-1) followed by NO3 (R ∼ 0.07 s-1) and O3 (R ∼ 2 × 10-5s-1). The missing OH reactivity was found to be large in accordance with measurements (∼ 65%) as would be expected from the chemical subset described in the model. The accounted OH radical sinks were inorganic compounds (∼ 41%, mainly due to reaction with CO), emitted monoterpenes (∼ 14%) and oxidised biogenic volatile organic compounds (∼ 44%). The missing reactivity is expected to be due to unknown biogenic volatile organic compounds and their photoproducts, indicating that the true main sink of OH is not expected to be inorganic compounds. The NO3 radical was found to react mainly with primary emitted monoterpenes (∼ 60%) and inorganic compounds (∼ 37%, including NO2). NO2 is, however, only a temporary sink of NO3 under the conditions of the campaign (with typical temperatures of 20–25 °C) and does not affect the NO3 concentration. We discuss the difference between instantaneous and steady-state reactivity and present the first boreal forest steady-state lifetime of NO3 (113 s). O3 almost exclusively reacts with inorganic compounds (∼ 91%, mainly NO, but also NO2 during night) and less with primary emitted sesquiterpenes (∼ 6%) and monoterpenes (∼ 3%). When considering the concentration of the oxidants investigated, we find that OH is the oxidant that is capable of removing organic compounds at a faster rate during daytime, whereas NO3 can remove organic molecules at a faster rate during night-time. O3 competes with OH and NO3 during a short period of time in the early morning (around 5 a.m. local time) and in the evening (around 7–8 p.m.). As part of this study, we developed a simple empirical parameterisation for conversion of measured spectral irradiance into actinic flux. Further, the meteorological conditions were evaluated using radiosonde observations and ground-based measurements. The overall vertical structure of the boundary layer is discussed, together with validation of the surface energy balance and turbulent fluxes. The sensible heat and momentum fluxes above the canopy were on average overestimated, while the latent heat flux was underestimated.